Urgensi Pengetahuan Sejarah Sosial Pendidikan Islam Dalam Dunia Akademis - Sutarjo, J (Tarbawiyah Jurnal Ilmiah Pendidikan, 2014)
This article describes the emergence of Islam that is automatically became a big movement in the world for changing the people's lives. The change is certainly not out of the educational process into the media changes. In the process of education, there are several elements that support the applying educational process in human life. it is mainly include education about the device; such as material and method in education. in addition explanation about objects and methods in Islamic education also elaborated on the importance of knowledge about education for generations in the future. This is important in order to take the impressions made footing especially concerning Islamic education. And for the ending of from this discourse is that Social History of Islamic education is the branch of science of the growth and development of Islamic education in terms of ideas, concepts, application of the institution since the time of the prophet Muhammad to the present study the social history of Islamic education are facts of Islamic education in the form of information about the growth and development of Islamic education either formal, informal and non-formal. The usefulness of the social history of Islamic education that is academically expected to; Knowing and understanding the growth and development of Islamic education, from the time of birth until the present, taking advantage of the Islamic educational process, in order to solve the problems of Islamic education in the present and have a positive attitude to changes and reforms the system of Islamic education.